Brasil: nunca mais – imprensa, transição política e memórias da ditadura - Silva, Amanda Romanelli (2021)
This dissertation aims to analyse how the press reported the release of Brasil: Nunca Mais and the denouncement of tortures and murders disclosed by the book in the year when Brazil elected a civilian president again, during the political transition towards democracy. Brasil: Nunca Mais is considered an important landmark on the Brazilian dictatorship memories, still a topic of discussion to the present days. Considered by many as the first Brazilian Truth Commission for exposing "tortures' stories, political prisoners’ murders, political persecutions, and biased trials" (ARQUIDIOCESE DE SÃO PAULO, 1985, p. 22), Brasil: Nunca Mais Project became a reference by denouncing the human rights violations in the military dictatorship. Brasil: Nunca Mais Project's research was produced between 1979 and 1985, and it originates a book also named Brasil: Nunca Mais, published in July 1985. The book aimed to publicise all the abuses committed by Brazilian repression after the 1964 coup d'état. The sources used in this research were criminal actions instituted in the Military Justice during the dictatorship, that is, official documentation produced by the repressive apparatus itself